Relações interpessoais positivas: um estudo etnográfico em uma escola municipal de Cascavel PR - Novello, Rejane (2020)
This study aimed to analyze the quality of interpersonal relationships in an elementary school in the town of Cascavel (PR), Brazil, which won first place in the Basic Education Development Index (IDEB) in 2017. For its elaboration, A research was carried out with an interdisciplinary approach, encompassing Sociology and Psychology, split into two moments. First, it was dedicate to a bibliographic survey regarding post-modernity, interpersonal relationships, school environment and teaching work. In order to situate the studied phenomenon, it was made a survey of constant theses and dissertations in the assets of Higher Education Personnel Improvement Coordination (CAPES) guided by the correlation between the thematic school violence and interpersonal relations in education, specifically, from the 80’s. In the second moment, an ethnographic field research was carried out in the participant observation modality. For its execution, field work was conducted, beginning on August 11th, 2010 and ending on October 30th, 2019, alternately (dates and shifts), and data collection from the interaction with teachers, school management, and school staff. Such interaction took place in the following spaces: library, cafeteria, lobby, front desk, the teachers’ room, the hour-activity room, the TI room, and the council’s room. In the logbook, speeches, actions, activities and informal conversations were recorded, which, subsequently, were transformed into data for analysis. The systematization, categorization and analysis of these data were guided by the methodology of Gibbs (2009). As a theoretical support, the following authors were used: Michel Maffesoli (1987; 2007; 2014; 2016), Georg Simmel (1983), Petrim Sorokin (1966), Edgar Morin (2001), Celso Antunes (2009; 2014), Maurice Tardif & Claude Lessard (2014), Adriano Moro – Grupo de estudos e pesquisa em educação moral - GEPEM (2018) and Marli Eliza D.A. de André (2012). This study allowed identifying positive forms of interpersonal relationships in the studied school. As a result of the analyzes, it was created six categories which constitute the institution: (i) cooperation; (ii) school management; (iii) work commitment; (iv) daily life organization; (v) interaction between schools; (vi) family and pleasant environment. It was concluded that the categories aforementioned contribute to a quality school climate and good learning results.